Análise espaço-temporal da malária no Estado do Pará no período de 2009 a 2018 - BRANDÃO, Rogério Gomes (2020)
Malaria is an acute febrile infectious disease, whose etiological agents are protozoa transmitted by vectors of the genus Anopheles. The present research aimed to analyze and demonstrate the distribution in space and time of malaria cases recorded in the state of Pará between 2009 and 2018. In this study, anua parasitic incidence (IPA) was used to classify the areas in the 144 municipalities of the state, and through a Geographic Information System (SIG), thematic and interpolation maps were constructed, relating the values of the incidence rates on their spatial location. Based on information from the Ministry of Health, the data were organized through graphs, maps and tables, in order to demonstrate the occurrence rates in the state, aiming at a better perception and understanding of the dynamics that the disease establishes throughout the Time. The areas with the highest concentration of the disease were distributed in the regions of Tapajós (Itaituba, Jacareacanga and Novo Progresso), Marajó and Tocantins (Anajás, Oeiras do Pará, Cametá, Breves, Curralinho, São Sebastião da Boa Vista, Portel and Bagre), with greater or lesser intensity over the years of study. Despite the decrease in the number of cases, the occurrence of registration in a recent past in the areas mentioned indicates the epidemiological potential for the disease to be disseminated again in municipalities considered to be controlled for malaria.